Austria : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report ;, 2018)
This paper evaluates the state of fiscal transparency in Austria. Austria has built strong fiscal institutions over the past decade, notably through the budget reforms introduced in 2009 and 2013, which have significantly improved fiscal transparency. Many elements of sound fiscal transparency practices are in place in Austria. Fiscal reports, covering a substantial part of public activities, are published in a frequent and timely manner and include reconciliations between alternative measures of fiscal aggregates. Budgets and forecasts have a clearer medium-term and performance-oriented focus, and are guided by clear fiscal policy objectives, the compliance with which is subject to independent scrutiny. In addition, there is regular, high-quality reporting on the long-term sustainability of public finances.